Perkembangan regulasi perbankan syariah di Indonesia - Al-Hakim, Sofyan (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Not only Islamic financial institutions rate impressively, but also Islamic banking. Statistics released by Bank Indonesia prove the premise. At the same time, supporting the legality of Islamic banking operations became more solid. Although at the beginning of its establishment faced legal problems, but since the enactment the Islamic Banking No. 21 of 2008 has been issued, the problem is resolved. Authority that important in the dynamics of Islamic banking regulation is the National Sharia BoardCouncil of Ulama Indonesia (DSN-MUI). The council became the source of authoritative institutions in guarding the observance of the Islamic banking industry to comply with the rules of sharia. All Islamic banking products must be controlled under sharia compliance by the DSN-MUI. Then, the fatwa is absorbed by Bank Indonesia and Bank Indonesia Regulation (Peraturan Bank Indonesia) is set to be. In this context, the national banking regulator has a significant association with DSN-MUI fatwa.